Conversational Implicature and Politeness Strategies in Bíọ́dún-Káyọ̀dé Newspapers’ Review in South Western Nigeria (American International Journal of Education and Linguistics Research, 2019)
Wardhaugh (1986) opines that when we speak, choices must of necessity be made of what we want to say, how we want to say it, the choice of words, sounds, (styles and other variables available within the speech community) that best unite (connect) what we say with how it is said.  Based on the foregoing, the focus of this study is to identify and analyze the politeness strategies employed in the talk exchanges presented in Bíọ́dún and Káyọ̀dé newspapers’ review through critical evaluation. In addition, the study seeks to investigate what is implicated by an expression, other than what a speaker actually said by saying what he said.  Brown and Levinson's politeness theory and Grice’s Cooperative Principle with its Maxims are adopted for analysis purpose. This study intends to show that Yorùbá culture places premium on social behaviour displayed and to reveal some of the culturally inherent linguistic and non-linguistic tools in the native speakers’​intuition as well as and repertoire of the people which they employ to meet the face want of interlocutors in communication situations.